Correlation between Nutritional Status and Age of Menarche in Adolescent at SMP 24 Surakarta - Endriansa, Chendy; Indriyati, .; Timor, Amandha Boy (Nexus Kedokteran Komunitas, 2015)
Background : Menarche occurs when a young woman entered the age of transition. Age of menarche is determined by several factors such as nutritional status. Nutrition affects sexual maturation in adolescents who received early menarche. In general, those who experienced early sexual maturity will have higher body mass index (BMI) and those with delayed sexual maturity has lower Body Mass Index at the same age. This study aimed to determine correlation between nutritional status and age of menarche in adolescent at SMP 24 Surakarta. Methods : This study used a cross sectional design. Respondent of this study was 100 female students of SMP 24 Surakarta selected with purposive random sampling. Data were collected by measuring BMI (Body Mass Index) and questionnaires, then analyzed by Chi Square test. Results : The number of respondents who have good nutrition aged 12-13 years is 44 students (44%) and aged >13 years is 19 students (19%). Meanwhile, the number of respondents who have poor nutrition aged 12-13 years is 16 students (16%) and aged >13 years is 21 students (21%). There is a significant correlation between nutritional status and age of menarche in adolescent at SMP 24 Surakarta (p = 0.009). Conclusions : There is a significant correlation between nutritional status and age of menarche. Female students which have a good nutritional status will experience menarche 3 times faster than female students which have a poor nutritional status. Keywords : Menarche, Nutritional Status, Adolescent, BMI